2014
DOI: 10.1039/c4nr01005a
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of fullerene-inhibited aggregation of Alzheimer's β-amyloid peptide fragment

Abstract: Amyloid deposits are implicated in the pathogenesis of many neurodegenerative diseases such as Alzheimer's disease (AD). The inhibition of β-sheet formation has been considered as the primary therapeutic strategy for AD. Increasing data show that nanoparticles can retard or promote the fibrillation of amyloid-β (Aβ) peptides depending on the physicochemical properties of nanoparticles, however, the underlying molecular mechanism remains elusive. In this study, our replica exchange molecular dynamics (REMD) sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(160 citation statements)
references
References 64 publications
(508 reference statements)
13
147
0
Order By: Relevance
“…Although easy to implement and perform, this method was shown to have a relatively large error range (Singh & Warshel, 2010) into the adsorption strength of a binding mode from a trajectory, a better sampling of configuration phase space is required for MD simulations. To reduce the effect of the insufficient sampling on the energy calculations, Xie et al (2014) used the REMD method for sampling the adsorption of the Aβ peptide to fullerenes. After clustering of the conformers, the MM-GBSA method was employed to obtain binding free energies for the largest clusters.…”
Section: Applications Of Free Energy Calculation Methods To Protein-smentioning
confidence: 99%
See 1 more Smart Citation
“…Although easy to implement and perform, this method was shown to have a relatively large error range (Singh & Warshel, 2010) into the adsorption strength of a binding mode from a trajectory, a better sampling of configuration phase space is required for MD simulations. To reduce the effect of the insufficient sampling on the energy calculations, Xie et al (2014) used the REMD method for sampling the adsorption of the Aβ peptide to fullerenes. After clustering of the conformers, the MM-GBSA method was employed to obtain binding free energies for the largest clusters.…”
Section: Applications Of Free Energy Calculation Methods To Protein-smentioning
confidence: 99%
“…Binding free energy calculations of amyloidogenic apoC-II(60-70) peptide on fullerene, CNT and graphene using MD simulations showed that the binding affinity was weakest for the fullerene and strongest for the graphene due to reduced efficiency of π-stacking interactions between the aromatic side chains of the peptide and the fullerene and CNT arising from the increased surface curvature (Todorova et al 2013). Xie et al (2014) calculated the adsorption free energies of Alzheimer's β-amyloid peptide fragments (Aβ) to two different fullerene nanoparticle systems, C 180 and three C 60 (3C 60 ). They found tighter binding of the peptides on the larger C 180 .…”
Section: Morphologymentioning
confidence: 99%
“…Moreover, the D23–K28 salt bridge in this site can be destabilized by DMF, which is thought to be significant in the Aβ fibrillation. Additionally, Xie et al studied the molecular mechanism of inhibition of Alzheimer's Aβ peptide aggregation by fullerene [48]. Their results showed that significantly higher inhibition of β-sheet formation through fullerene is due to extreme lipophilic and aromatic π -stacking interactions of the C 60 hexagonal rings.…”
Section: Nanotechnology Based Theranostics In Admentioning
confidence: 99%
“…It was reported that strong interactions between the fullerene NPs and Aβ 16–22 fragments significantly weakened peptide-peptide contact, thus limiting amyloid fibrillization. 123 An additional study conducted by Sun et al investigated the effect of DMF on the conformation of Aβ 1–42 dimer. Computational simulations indicated that the interaction of DMFs with Aβ peptides also greatly impeded the formation of β-hairpins and inter-peptide β-sheets.…”
Section: Amyloid-mediated Cytotoxicity and Mitigation With Nanomaterialsmentioning
confidence: 99%